Industrial attachment report development of Pipeline Simulator Model - Hikaru, Fujishima. (2008)
The System Engineering (SE) division of the Defence Science & Technology Agency (DSTA) provides analysis and solutions for military logistics optimisation. The Pipeline Simulator (Piper), an in-house developed simulation software, was designed to solve difficult spares optimisation problems for the Singapore Armed Forces (SAF).